Perovskite passivation material, passivation unit and perovskite battery

Through spin coating and annealing cross-linking technology of vinylthiophene compounds, the problem of uncoordinated ions on the surface of perovskite solar cells is solved, and the stability and electrochemical performance are improved, which is suitable for commercial applications.

CN119277948APending Publication Date: 2025-01-07TRINA SOLAR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411356881.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The stability problems of perovskite solar cells are mainly due to the fact that the bare ions on the uncoordinated surface of perovskite are prone to polarization reactions during preparation and use, resulting in interface defects and layer degradation. The existing passivation method is expensive or affects charge extraction. and transport, and fail to effectively solve the passivation problem of uncoordinated ions.

Method used

Vinylthiophene compounds are used as passivation materials, and uniform films are formed through spin coating technology, and cross-linking reactions are carried out during the annealing process to form a stable network structure, enhance the binding force with the perovskite layer, and achieve effective passivation.

Benefits of technology

The stability and long-term effectiveness of the passivation layer are achieved, the electrochemical performance of perovskite batteries is improved, the photoelectric conversion efficiency and stability is significantly improved, the manufacturing cost is reduced, and it is suitable for commercial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119277948A_ABST
    Figure CN119277948A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cell interface modification, and particularly provides a perovskite passivation material, a passivation unit and a perovskite cell. The perovskite passivation material provided by the invention comprises a vinyl thiophene compound. According to the invention, the perovskite layer is passivated and modified through the vinyl thiophene compound, and the passivation layer has a good passivation effect and effectively passivates defects in the perovskite layer; and high stability is achieved, the long-term effectiveness of the passivation layer is guaranteed, and the passivation effect can be stably kept for a long time. The passivation layer can greatly improve the photoelectric conversion efficiency of the device, and provides powerful support for the development of the fields of perovskite solar cells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of interface modification of perovskite solar cells, and specifically provides a perovskite passivation material, a passivation unit and a perovskite cell. Background Art

[0002] After more than ten years of development, organic-inorganic hybrid perovskite solar cells are now in the process of commercialization. However, the stability of perovskite solar cells is still a key technical point that needs to be solved urgently. Uncoordinated exposed ions on the surface of perovskites are prone to polarization reactions during the preparation process and the use of devices, resulting in interface defects, inducing degradation of the perovskite layer, and ultimately causing the device to gradually fail. Studies have shown that interface engineering in perovskite solar cell devices has a huge impact on the devices. Reducing non-radiative carrier recombination at the surface / interface and increasing carrier lifetime are effective ways to optimize perovskite cell devices. Among them, interface passivation is a simple, effective, and easy-to-commercialize method in interface engineering.

[0003] There are some problems with the existing methods for passivating the surface of perovskite. For example, some solutions require micro-etching of the surface of the perovskite layer, which increases the preparation cost; some use ammonium salts to treat the perovskite surface to form a two-dimensional perovskite layer to reduce surface defects, but the two-dimensional perovskite layer affects the charge extraction and transmission at the interface to a certain extent, which may have an adverse effect on device performance; others introduce hydrophobic small molecule cross-linking agents into the perovskite precursor solution to improve the barrier to water vapor, but it is essentially similar to encapsulation and does not achieve a passivation effect on the uncoordinated ions on the perovskite surface.

[0004] Therefore, it is necessary to develop a technology that can effectively passivate the perovskite surface and stably maintain the passivation effect. Summary of the invention

[0005] In order to overcome the above defects, the present invention provides a perovskite passivation material, a passivation unit and a perovskite battery, which effectively passivate the defects on the perovskite surface by forming a stable passivation layer.

[0006] In a first aspect, the present invention provides a perovskite passivation material, comprising:

[0007] Vinylthiophene compounds.

[0008] Furthermore, the structural formula of the vinylthiophene compound is:

[0009] in

[0010] R1 is selected from hydrogen, halogen, alcohol, carboxyl or substituted or unsubstituted alkyl;

[0011] R2 is selected from hydrogen, halogen or aldehyde;

[0012] R3 is selected from alcohol, halogen, carboxyl or substituted or unsubstituted alkyl;

[0013] R4 is selected from halogen or substituted or unsubstituted alkyl;

[0014] R5 is selected from carboxyl or substituted or unsubstituted alkyl;

[0015] R6 is selected from halogen, carboxyl, and substituted or unsubstituted alkyl.

[0016] Furthermore, the alkyl groups in R1, R3, R4, R5 and R6 are each independently selected from C1-C5 alkyl groups.

[0017] Furthermore, the vinylthiophene compound comprises:

[0018] One or more of 2-vinylthiophene, 4-chloro-2-vinylthiophene, 3-vinylthiophene, 2-(2,2-dibromovinyl)thiophene, 2-bromo-5-vinylthiophene, 2-methyl-5-vinylthiophene, 5-formyl-2-(2,2-dicyanovinyl)thiophene and 2-bromo-5-(2,2-dibromovinyl)thiophene.

[0019] In a second aspect, the present invention provides a passivation unit for a perovskite battery, comprising:

[0020] Perovskite layer;

[0021] A passivation layer is formed on the perovskite layer, wherein the passivation layer is obtained according to the perovskite passivation material described in the first aspect.

[0022] Furthermore, the thickness of the passivation layer is 1-100 nm.

[0023] In a third aspect, the present invention provides a method for preparing a passivation unit of a perovskite battery, comprising:

[0024] Forming a perovskite layer;

[0025] Prepare a passivation layer solution according to the perovskite passivation material of the first aspect;

[0026] A passivation layer is formed on the perovskite layer based on the passivation layer solution.

[0027] Furthermore, the preparation method of the passivation layer solution includes:

[0028] The perovskite passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution.

[0029] Furthermore, the concentration of the passivation layer solution is 0.5 mg / mL-5 mg / ml.

[0030] Further, forming a passivation layer on the perovskite layer based on the passivation layer solution comprises:

[0031] The passivation layer solution is spin-coated on the perovskite layer to form a passivation layer.

[0032] Further, the spin coating method comprises:

[0033] Spin at a preset speed.

[0034] Furthermore, the preset rotation speed is 2000-5000 rpm, and the duration is 20-50 seconds.

[0035] Furthermore, after the step of spin coating the passivation layer solution on the perovskite layer, the method further comprises:

[0036] Anneal at a preset temperature.

[0037] Furthermore, the preset temperature is 50-100° C., and the annealing time is 10-30 min.

[0038] In a fourth aspect, the present invention provides a perovskite battery, comprising:

[0039] substrate;

[0040] A first electrode formed on the substrate;

[0041] a first transmission layer formed on the first electrode;

[0042] A passivation unit according to the second aspect or a passivation unit of a perovskite cell prepared by the preparation method of the third aspect, wherein the passivation layer is arranged close to the second transmission layer;

[0043] a second transmission layer formed on the passivation unit;

[0044] The second electrode is formed on the second transmission layer.

[0045] Furthermore, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.

[0046] Furthermore, the battery further comprises a hole blocking layer, wherein the hole blocking layer is formed on the electron transport layer, and the second electrode is formed on the hole blocking layer.

[0047] The above one or more technical solutions of the present invention have at least one or more of the following beneficial effects:

[0048] The present invention selects vinylthiophene compounds as interface passivation modification materials, firstly, the vinylthiophene compounds are uniformly deposited on the surface of the perovskite layer by spin coating technology, so as to ensure that the vinylthiophene compounds form a uniform and dense film on the surface of the perovskite layer. Next, an annealing process is adopted, and the annealing process causes the passivation molecules in the film to undergo a cross-linking reaction at a high temperature, thereby forming a stable network structure, which can not only enhance the binding force between the passivation molecules and the perovskite layer, but also effectively prevent the passivation molecules from falling off or migrating during subsequent applications, and finally form a stable and effective passivation layer.

[0049] The obtained passivation layer not only has a good passivation effect and effectively passivates the defects in the perovskite layer; it also has high stability, which ensures the long-term effectiveness of the passivation layer and enables the passivation effect to be maintained for a long time and stably, thereby improving the electrochemical performance of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The disclosure of the present invention will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In addition, similar numbers in the figures are used to represent similar components, among which:

[0051] Figure 1 is a schematic flow chart of main steps of a method for preparing a passivation unit according to an embodiment of the present invention;

[0052] Figure 2 is a schematic diagram of the main structure of a perovskite battery according to an embodiment of the present invention;

[0053] Figure 3 Schematic diagram of cross-linking of vinylthiophene compounds according to one embodiment of the present invention. DETAILED DESCRIPTION

[0054] Some embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0055] The present invention provides a perovskite passivation material, comprising:

[0056] Vinylthiophene compounds.

[0057] The vinylthiophene compounds at least include vinyl and thiophene / thiophene derivatives.

[0058] Vinylthiophene compounds have a simple molecular structure and low cost. The lone pair of electrons on their nitrogen atoms can coordinate with uncoordinated lead ions to achieve defect passivation. At the same time, the presence of vinyl groups enables vinylthiophene to achieve in-situ thermal cross-linking during the annealing process of perovskite battery preparation, thereby enhancing the stability of the coordinated passivation layer.

[0059] In one embodiment, the structural formula of the vinylthiophene compound is: in

[0060] R1 is selected from hydrogen, halogen, alcohol, carboxyl or substituted or unsubstituted alkyl;

[0061] R2 is selected from hydrogen, halogen or aldehyde;

[0062] R3 is selected from alcohol, halogen, carboxyl or substituted or unsubstituted alkyl;

[0063] R4 is selected from halogen or substituted or unsubstituted alkyl;

[0064] R5 is selected from carboxyl or substituted or unsubstituted alkyl;

[0065] R6 is selected from halogen, carboxyl, and substituted or unsubstituted alkyl.

[0066] In one embodiment, the alkyl group of R1 is selected from C1-C5 alkyl groups; the alkyl group of R3 is selected from C1-C5 alkyl groups; the alkyl group of R4 is selected from C1-C5 alkyl groups; the alkyl group of R5 is selected from C1-C5 alkyl groups; and the alkyl groups of R6 are each independently selected from C1-C5 alkyl groups.

[0067] In one embodiment, the vinylthiophene compound comprises:

[0068] One or more of 2-vinylthiophene, 4-chloro-2-vinylthiophene, 3-vinylthiophene, 2-(2,2-dibromovinyl)thiophene, 2-bromo-5-vinylthiophene, 2-methyl-5-vinylthiophene, 5-formyl-2-(2,2-dicyanovinyl)thiophene and 2-bromo-5-(2,2-dibromovinyl)thiophene.

[0069] The present invention also provides a passivation unit for a perovskite battery, comprising:

[0070] Perovskite layer;

[0071] A passivation layer is formed on the perovskite layer, wherein the passivation layer is obtained according to the perovskite passivation material.

[0072] The present invention passivates and modifies the perovskite layer by using vinylthiophene compounds. The passivation layer not only has a good passivation effect and effectively passivates the defects in the perovskite layer, but also has high stability, ensuring the long-term effectiveness of the passivation layer, and can maintain the passivation effect for a long time and stably. This passivation layer can greatly improve the photoelectric conversion efficiency of the device, providing strong support for the development of fields such as perovskite solar cells.

[0073] In one embodiment, the thickness of the passivation layer is 1-100 nm.

[0074] Increasing the thickness of the passivation layer will enhance the passivation effect, but at the same time, as the thickness increases, the current transmission channel will be limited, resulting in a decrease in current transmission efficiency. Therefore, by precisely controlling the thickness of the passivation layer, it is possible to enhance the passivation effect while avoiding the problem of limited current transmission, thereby optimizing the performance of the material.

[0075] The present invention also provides a method for preparing a passivation unit of a perovskite battery, referring to Figure 1 ,include:

[0076] S1, formation of perovskite layer;

[0077] S2, preparing a passivation layer solution according to the perovskite passivation material;

[0078] S3, forming a passivation layer on the perovskite layer based on the passivation layer solution.

[0079] In one embodiment, the method for preparing the passivation layer solution in step S2 includes:

[0080] The perovskite passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution. The solution may be selected from ether, isopropanol, ethyl acetate, chlorobenzene or ethanol.

[0081] In one embodiment, the concentration of the passivation layer solution is 0.5 mg / L-5 mg / ml.

[0082] In one application scenario, the concentration of the passivation layer solution is 1 mg / L.

[0083] In one embodiment, in step S3, forming a passivation layer on the perovskite layer based on the passivation layer solution includes:

[0084] The passivation layer solution is spin-coated on the perovskite layer to form a passivation layer.

[0085] In one embodiment, the spin coating method includes:

[0086] Spin at a preset speed.

[0087] In one embodiment, the preset rotation speed is 2000-5000 rpm, and the duration is 20-50 seconds.

[0088] In one application scenario, the preset rotation speed is 3000 rpm and the duration is 30 seconds.

[0089] In one embodiment, after the step of spin coating the passivation layer solution on the perovskite layer, the method further comprises:

[0090] Anneal at a preset temperature.

[0091] In one embodiment, the preset temperature is 50-100° C., and the annealing time is 10-30 min.

[0092] In one application scenario, annealing is performed at 50°C for 30 minutes.

[0093] The present invention selects vinylthiophene compounds as interface passivation modification materials, firstly, the vinylthiophene compounds are uniformly deposited on the surface of the perovskite layer by spin coating technology to ensure that the vinylthiophene compounds form a uniform and dense film on the surface of the perovskite layer. Next, an annealing process is used. The annealing process allows the passivation molecules in the film to undergo a cross-linking reaction at high temperature, thereby forming a stable network structure, which can not only enhance the binding force between the passivation molecules and the perovskite layer, but also effectively prevent the passivation molecules from falling off or migrating during subsequent applications, and finally form a stable and effective passivation layer.

[0094] The present invention discloses a perovskite battery, comprising a substrate 1, a first electrode 2, a first transmission layer 3, a passivation unit 4, a second transmission layer 5 and a second electrode 6 stacked from bottom to top. Figure 2 , the battery includes:

[0095] Substrate 1;

[0096] The first electrode 2 is formed on the substrate.

[0097] The first transmission layer 3 is formed on the first electrode.

[0098] The passivation unit 4 or the passivation unit of the perovskite battery prepared by the preparation method, wherein the passivation layer 4 - 1 is arranged close to the second transmission layer 5 , and the perovskite layer 4 - 2 is arranged close to the first transmission layer 3 .

[0099] The second transmission layer 5 is formed on the passivation unit 4 .

[0100] The second electrode 6 is formed on the second transmission layer 5 .

[0101] In one embodiment, the first transport layer 3 is a hole transport layer, and the second transport layer 5 is an electron transport layer.

[0102] In one embodiment, the material of the electron transport layer is selected from [6,6]-phenyl-C61-butyric acid methyl ester, C 60 and tin oxide.

[0103] The perovskite layer is a perovskite light-absorbing layer, and its material comprises a first perovskite material and a second perovskite material; wherein the mass ratio of the first perovskite material to the second perovskite material is (0.9-1.2): 1. The first perovskite material is selected from at least one of a lead halide salt and a tin halide salt, and the second perovskite material is selected from at least one of a formamidine halide salt, a methylamine halide salt, and a cesium halide salt.

[0104] The material of the hole blocking layer is selected from 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or zirconium acetylacetonate.

[0105] The first electrode is selected from conductive glass, including TCO conductive glass.

[0106] The second electrode comprises a metal electrode, and the electrode material is selected from at least one of silver, copper, conductive oxide and carbon electrode.

[0107] In one embodiment, the battery further includes a hole blocking layer, wherein the hole blocking layer is formed on the electron transport layer, and the second electrode is formed on the hole blocking layer.

[0108] The perovskite passivation material of the present invention is used in a perovskite photoelectric device to improve the electrochemical performance of the device. The perovskite photoelectric device is a perovskite solar cell or module.

[0109] Next, the perovskite solar cell was prepared using the perovskite passivation material of the present invention, and its cell performance was tested.

[0110] Example 1

[0111] The process of preparing a perovskite solar cell in this embodiment includes:

[0112] (1) The TCO conductive glass was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 minutes respectively, and finally dried in a drying oven at 75°C for later use; the dried TCO glass substrate was placed in a UV ozone machine for 25 minutes to remove organic impurities on its surface and optimize its surface wettability.

[0113] (2) 1 mg of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid was dissolved in 1 mL of isopropanol to prepare a hole transport material solution. The hole transport material solution was coated on a TCO glass substrate and then annealed at 100° C. for 10 minutes to form a hole transport layer.

[0114] (3) Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF), and stir at room temperature until completely dissolved to obtain a perovskite precursor solution; in a nitrogen glove box, take 30 μL of the perovskite precursor solution and drop it onto the ITO conductive glass that forms the hole transport layer, first spin-coat it at 1000 rpm for 10 s, then spin-coat it at 5000 rpm for 30 s. During this process, quickly add 125 μL of chlorobenzene after 25 s, and then place the TCO glass on a hot stage and heat and anneal it at 100 °C for 40 min to form a 500 nm perovskite light-absorbing layer.

[0115] (4) 5 mg of 2-vinylthiophene (molecular formula C 6 H 6 S) was dissolved in 5 mL of ether and stirred at room temperature in the dark until dissolved to obtain a passivation layer solution. The above solution was dynamically spin-coated and deposited on the surface of the perovskite layer at a speed of 3000 rpm for 30 seconds, and then annealed at 50° C. for 30 minutes to cross-link the passivation molecules to obtain a passivation layer with a thickness of 58 nm.

[0116] (5) Dissolve 20 mg of methanefullerene phenyl-C61-butyric acid methyl ester (PCBM) in 1 mL of chlorobenzene and stir at room temperature to obtain [6,6]-phenyl-C61-butyric acid methyl ester solution; take 30 μL of [6,6]-phenyl-C61-butyric acid methyl ester solution and spin coat it on the ITO conductive glass with a perovskite light absorption layer at 3000 rpm for 60 seconds to form a 30 nm electron transport layer.

[0117] (6) Dissolve 0.5 mg of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in 1 mL of isopropanol and stir at room temperature to obtain a hole blocking layer solution; take 40 μL of the hole blocking layer solution and drop it onto the electron transport layer, and spin coat at 5000 rpm for 35 s to form a hole blocking layer of 6 nm.

[0118] (7) The TCO conductive glass formed with the hole blocking layer, electron transport layer, interface modified passivation layer, perovskite light absorption layer (i.e., perovskite layer), and hole transport layer is transferred to the vacuum coating instrument and the vacuum degree is drawn to 3*10 -4 A silver electrode was evaporated at 400 ℃ and 100 nm thick on the hole blocking layer to obtain an electrode layer.

[0119] Thus, the perovskite cell of Example 1 was prepared.

[0120] Example 2

[0121] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0122] Step (4) is to dissolve 5 mg of 3-vinylthiophene in 5 mL of ether, stir at room temperature in the dark until dissolved, to obtain a passivation layer solution, take uL of the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 2000 rpm for 50 seconds, and then anneal at 80°C for 10 minutes to cross-link the passivation molecules.

[0123] Example 3

[0124] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0125] Step (4) is to dissolve 5 mg of 2-bromo-5-vinylthiophene in 5 mL of ether, stir at room temperature in the dark until dissolved, to obtain a passivation layer solution, take the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 5000 rpm for 20 seconds, and then anneal at 100° C. for 12 minutes to cross-link the passivation molecules.

[0126] Example 4

[0127] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0128] Step (4) is to dissolve 5 mg of 2-bromo-5-vinylthiophene in 5 mL of isopropanol, stir at room temperature in the dark until dissolved, to obtain a passivation layer solution, take the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 4000 rpm for 30 seconds, and then anneal at 70°C for 20 minutes to cross-link the passivation molecules.

[0129] Example 5

[0130] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0131] Step (4) Dissolve 5 mg of 2-vinylthiophene in 10 mL of ether, stir at room temperature in the dark until dissolved, and obtain a passivation layer solution. Take the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 3000 rpm for 30 seconds, then anneal at 50° C. for 30 minutes to cross-link the passivation molecules, and obtain a passivation layer with a thickness of 16 nm.

[0132] Example 6

[0133] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0134] Step (4) Dissolve 10 mg of 2-vinylthiophene in 5 mL of ether, stir at room temperature in the dark until dissolved, and obtain a passivation layer solution. Take the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 3000 rpm for 30 seconds, then anneal at 50° C. for 30 minutes to cross-link the passivation molecules, and obtain a passivation layer with a thickness of 76 nm.

[0135] Example 7

[0136] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that:

[0137] Step (4) Dissolve 10 mg of 2-vinylthiophene in 2 mL of ether, stir at room temperature in the dark until dissolved, and obtain a passivation layer solution. Take the above solution and dynamically spin-coat it on the surface of the perovskite layer at a speed of 3000 rpm for 30 seconds, then anneal at 50° C. for 30 minutes to cross-link the passivation molecules, and obtain a passivation layer with a thickness of 98 nm.

[0138] Comparative Example 1

[0139] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that no passivation layer is used.

[0140] The preparation process of Comparative Example 1 does not involve step (4), but after forming the perovskite light absorbing layer in step (3), an electron transport layer in step (5) is formed on the perovskite light absorbing layer.

[0141] Comparative Example 2

[0142] This embodiment provides a method for preparing a perovskite solar cell. The preparation steps thereof are different from those of Embodiment 1 in that 2-vinylthiophene in step (4) is replaced by poly(3-hexylthiophene).

[0143] Comparative Example 3

[0144] This embodiment provides a method for preparing a perovskite solar cell, and the preparation steps thereof are different from those of Embodiment 1 in that 2-vinylthiophene in step (4) is replaced by 2-vinylimidazole.

[0145] The perovskite solar cells obtained in the above-mentioned embodiments 1-7 and comparative examples 1-3 were subjected to electrochemical performance tests. In addition to the open circuit voltage, short circuit current, and fill factor, which characterize the electrochemical performance of the perovskite cell, the present invention also conducted a photoelectric conversion efficiency test and normalized the test method. The photoelectric conversion efficiency test was as follows: the perovskite solar cells obtained in each embodiment and comparative example were tested for stability performance at 85°C. Specifically, the device was placed on a hot stage and heated at 85°C for 1200h before the efficiency test was conducted; normalized efficiency = energy conversion efficiency after heating / energy conversion efficiency before heating × 100%, and the stability of the solar cell was tested by normalized efficiency. The test results are shown in Table 1.

[0146] Table 1 Battery performance test

[0147]

[0148] After an in-depth analysis of the data in Table 1, it can be clearly seen that compared with the unpassivated perovskite surface of Comparative Example 1, after the passivation material is added to the perovskite surface and treated, the photoelectric conversion efficiency of the device has been significantly improved. The photoelectric conversion efficiency of the perovskite surface device that has not been passivated is generally low. This is mainly because there are a large number of defects and dangling bonds on the perovskite surface, which will cause the recombination of electron-hole pairs, thereby reducing the photoelectric conversion efficiency. The photoelectric conversion efficiency of the device after the post-treatment with the passivation material has been greatly improved, indicating that the passivation of the perovskite surface is crucial to improving the performance of the device. However, different passivation technologies have different effects on improving device performance. It is not possible to achieve an improvement in device performance or an overall improvement simply by adding a passivation material.

[0149] Examples 1-7 add the passivation material of the vinylthiophene compound of the present invention. This innovative improvement significantly improves the electrochemical performance of the battery, especially in the stability of the solar cell. The electrochemical performance of the battery is improved in a comprehensive manner, including higher open circuit voltage, short circuit current and fill factor. In addition, the photoelectric conversion efficiency, which characterizes the stability of the solar cell, is significantly improved.

[0150] First, the overall improvement of battery electrochemical performance is explained, including:

[0151] 1. Increase of open circuit voltage:

[0152] Open circuit voltage is one of the important indicators for measuring battery performance. By adding vinylthiophene compound passivation materials, the open circuit voltage of the battery has been significantly improved. This improvement means that the battery can store more energy under no-load conditions, thereby providing a more stable current during discharge.

[0153] 2. Increase of short-circuit current:

[0154] The short-circuit current is the output current of the battery under short-circuit conditions, and its magnitude is directly related to the output capacity of the battery. The innovative improvements in Examples 1-7 significantly increase the short-circuit current of the battery, thereby improving the output performance of the battery.

[0155] 3. Optimization of fill factor:

[0156] The fill factor is an important parameter to measure the energy conversion efficiency of a battery. The higher the value, the better the performance of the battery. By adding vinylthiophene compound passivation materials, the fill factor of the battery is optimized, making the battery more efficient in the energy conversion process.

[0157] Here's a Breakthrough in Solar Cell Stability

[0158] 1. Improvement of stability and photoelectric conversion efficiency:

[0159] The stability of solar cells is a key indicator for measuring their long-term performance. The vinylthiophene compound passivation material in the present invention significantly improves the photoelectric conversion efficiency that characterizes the stability of solar cells. This means that the battery can maintain a high photoelectric conversion efficiency during long-term use, thereby extending the service life of the battery.

[0160] 2. Improvement of anti-aging performance:

[0161] The application of vinylthiophene compound passivation materials also makes solar cells have better anti-aging performance. In harsh environments, the battery can maintain stable performance and is not easily affected by external factors, thus ensuring its long-term stable operation.

[0162] In summary, Examples 1-7 achieve a comprehensive improvement in the electrochemical performance of the battery by adding vinylthiophene compound passivation materials, especially a breakthrough in the stability of solar cells, which provides strong support for the development of perovskite solar cell technology.

[0163] The above effects are mainly produced because in the perovskite passivation material of the present invention:

[0164] (1) Thiophene sulfur atoms can form a stable coordination passivation effect with uncoordinated lead ions in the perovskite layer; (2) The presence of vinyl groups can enable in situ thermal crosslinking of such passivation molecules, thereby enhancing the stability of the passivation layer; (3) After the vinyl thiophene compounds form a passivation layer, they have good hydrophobicity and water vapor barrier properties, thereby improving the perovskite layer's tolerance to water vapor.

[0165] In addition, vinylthiophene molecules have the advantages of simple structure, low cost, and easy promotion. Vinylthiophene molecules are generally low in cost, which helps to reduce the manufacturing cost of solar cells and make them more competitive in the market. The passivation material of the present invention is used to prepare perovskite cells, and the synthesis process is simple and convenient for industrial production.

[0166] It should be noted that the passivation effect in the embodiments of the present invention is not only significant, but also can be maintained and stable for a long time. In practical applications, this long-term stability is more important than the simple passivation effect. Because even if the passivation effect is very ideal in the short term, if it cannot be maintained for a long time, it cannot meet the needs of practical applications. The invention creatively obtains a good passivation effect by referring to Figure 3 , cross-linkable vinylthiophene small molecules are chemically fixed to the surface of the perovskite through the coordination effect, and then after heat treatment, they are in situ cross-linked to form a continuous polymer network that is more solid than using the polymer alone (such as Comparative Example 2) as a passivation material, thereby greatly passivating defects and obtaining a high-performance and high-stability device.

[0167] In Comparative Examples 2 and 3, since no in-situ crosslinking of vinylthiophene was performed, the passivation material could not form a stable chemical bond with the perovskite surface. This crosslinking process enables the passivation material to be tightly covered on the perovskite surface, thereby effectively reducing surface defects and surface state density. The chemical fixation process further strengthens the binding force between the passivation material and the perovskite surface. As a result, the passivation materials of Comparative Examples 2 and 3 cannot form a stable bond with the perovskite surface, resulting in a significant reduction in their passivation effect. The passivation material that has not been in-situ crosslinked and chemically fixed is prone to fall off or migrate during battery operation, which seriously affects the stability of the battery and cannot meet the requirements of long-term stable operation.

[0168] The present invention successfully achieves stable fixation of the passivation material by introducing the in-situ crosslinking and chemical fixation process of vinylthiophene on the perovskite surface, thereby achieving excellent passivation effect and high performance and high stability of the device. This innovative technological breakthrough provides an important guarantee for the commercial application of perovskite solar cells.

[0169] It should be pointed out that although the various steps in the above embodiments are described in a specific order, those skilled in the art can understand that in order to achieve the effects of the present invention, different steps do not have to be performed in such an order. They can be performed simultaneously (in parallel) or in other orders. These changes are within the scope of protection of the present invention.

[0170] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

Claims

1. A perovskite passivation material, characterized in that: include: Vinylthiophene compounds.

2. The material according to claim 1, characterized in that The structural formula of the vinylthiophene compound is: in R1 is selected from hydrogen, halogen, alcohol, carboxyl or substituted or unsubstituted alkyl; R2 is selected from hydrogen, halogen or aldehyde; R3 is selected from alcohol, halogen, carboxyl or substituted or unsubstituted alkyl; R4 is selected from halogen or substituted or unsubstituted alkyl; R5 is selected from carboxyl or substituted or unsubstituted alkyl; R6 is selected from halogen, carboxyl, and substituted or unsubstituted alkyl.

3. The material according to claim 2, characterized in that The alkyl groups in R1, R3, R4, R5 and R6 are each independently selected from C1-C5 alkyl groups.

4. The material according to claim 3, characterized in that The vinylthiophene compounds include: One or more of 2-vinylthiophene, 4-chloro-2-vinylthiophene, 3-vinylthiophene, 2-(2,2-dibromovinyl)thiophene, 2-bromo-5-vinylthiophene, 2-methyl-5-vinylthiophene, 5-formyl-2-(2,2-dicyanovinyl)thiophene and 2-bromo-5-(2,2-dibromovinyl)thiophene.

5. A passivation unit for a perovskite battery, comprising: Perovskite layer; A passivation layer is formed on the perovskite layer, wherein the passivation layer is obtained from the perovskite passivation material according to any one of claims 1 to 4.

6. The unit according to claim 5, characterized in that The thickness of the passivation layer is 1-100 nm.

7. A method for preparing a passivation unit of a perovskite battery, characterized in that: include: Forming a perovskite layer; Prepare a passivation layer solution according to the perovskite passivation material according to any one of claims 1 to 4; A passivation layer is formed on the perovskite layer based on the passivation layer solution.

8. The method according to claim 7, characterized in that The preparation method of the passivation layer solution comprises: The perovskite passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution.

9. The method according to claim 8, characterized in that The concentration of the passivation layer solution is 0.5 mg / mL-5 mg / ml.

10. The method according to claim 7, characterized in that The forming of a passivation layer on the perovskite layer based on the passivation layer solution comprises: The passivation layer solution is spin-coated on the perovskite layer to form a passivation layer.

11. The method according to claim 10, characterized in that Spin coating methods include: Spin at a preset speed.

12. The method according to claim 11, characterized in that The preset rotation speed is 2000-5000 rpm, and the duration is 20-50 seconds.

13. The method according to claim 10, characterized in that After the step of spin coating the passivation layer solution on the perovskite layer, the method further comprises: Anneal at a preset temperature.

14. The method according to claim 13, characterized in that The preset temperature is 50-100° C., and the annealing time is 10-30 minutes.

15. A perovskite battery, characterized in that: include: substrate; A first electrode formed on the substrate; The first transmission layer is formed on the first electrode.

16. A passivation unit for a perovskite battery prepared according to claim 5 or 6 or using the preparation method of any one of claims 7 to 14, wherein: The passivation layer is disposed close to the second transmission layer; a second transmission layer formed on the passivation unit; The second electrode is formed on the second transmission layer.

17. The battery according to claim 16, characterized in that The first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.

18. The battery according to claim 17, characterized in that The battery further includes a hole blocking layer, wherein the hole blocking layer is formed on the electron transport layer, and the second electrode is formed on the hole blocking layer.

Citation Information

Cited By

  • Perovskite passivation material, passivation layer and cell thereof

    CN119859116A

  • A perovskite passivation material, passivation layer and cell thereof

    CN119859116B